2019
DOI: 10.3390/foods9010003
|View full text |Cite
|
Sign up to set email alerts
|

Stone Milling versus Roller Milling in Soft Wheat: Influence on Products Composition

Abstract: Wholegrain wheat flours are in great demand from consumers worldwide because they are considered healthier then refined flours. They can be obtained by either stone milling, which is experiencing a revival in Europe, or roller milling. In order to study compositional differences due to the milling technology and to explore the possibility of a better qualification of wholegrain flours by means of nutritionally oriented quality parameters, eight mixes of soft wheat grains were stone milled and roller milled and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
2
10
1
Order By: Relevance
“…This is supported by the results of Carcea et al. (2019), who found that flours obtained with stone mills have a higher percentage of fractions with smaller particle size. However, the bran obtained from the roller milling process may also be reworked or micronized before being incorporated back into the flour from the endosperm.…”
Section: Wwf Chemical Compositionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is supported by the results of Carcea et al. (2019), who found that flours obtained with stone mills have a higher percentage of fractions with smaller particle size. However, the bran obtained from the roller milling process may also be reworked or micronized before being incorporated back into the flour from the endosperm.…”
Section: Wwf Chemical Compositionsupporting
confidence: 75%
“…Roller mills reduce particle size of endosperm flour while maintaining the bran particles in relatively large pieces, while stone and hammer mills lack this system (Posner & Hibbs, 2005). This is supported by the results of Carcea et al (2019), who found that flours obtained with stone mills have a higher percentage of fractions with smaller particle size. However, the bran obtained from the roller milling process may also be reworked or micronized before being incorporated back into the flour from the endosperm.…”
Section: Differences According To the Milling Processmentioning
confidence: 78%
“…In accordance with the AACC International definition of whole grain [33], neither milling process selected the anatomical regions, and endosperm, bran and germ have to be present in the same proportions as in the intact caryopsis. In agreement with other authors [17,20,22], no significant changes in the proximate composition were found regardless of the milling process used ( Table 3). The few differences between SWFs and RWFs concerned moisture, which was significantly higher in RWFs from Bona Vita and Skorpion cvs.…”
Section: Discussionsupporting
confidence: 93%
“…Although the occurrence of several macronutrients was unchanged in the compared WFs, RWFs of pigmented cvs resulted in a higher content of antioxidant compounds than SWF. Carcea et al [20] reported no compositional difference regarding the total polyphenol and alkylresorcinol contents between stone milled or roller milled flours. In our study, in particular, a significantly higher content of CWBPAs and TAC were present in RWFs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation